2018
DOI: 10.3847/2041-8213/aab2a5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Propagating Fast Sausage Waves through Detailed Analysis of a Zebra-pattern Fine Structure in a Solar Radio Burst

Abstract: Various magnetohydrodynamic (MHD) waves have recently been detected in the solar corona and investigated intensively in the context of coronal heating and coronal seismology. In this Letter, we report the first detection of short-period propagating fast sausage mode waves in a metric radio spectral fine structure observed with the Assembly of Metric-band Aperture Telescope and Real-time Analysis System. Analysis of Zebra patterns (ZPs) in a type-IV burst revealed a quasi-periodic modulation in the frequency se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
4
23
0
Order By: Relevance
“…Since an MHD oscillation affects the local values of the magnetic field and/or plasma density (and hence fce and/or fpe), the locations of the double plasma resonance layers are changed accordingly, which should result in periodic oscillations ("wiggles") of the zebra stripes. These wiggles were indeed observed in many events (e.g., Yu et al 2013;Kaneda et al 2018;Karlický and Yasnov 2020). The observed periods of oscillations (∼ 0.5 − 2 s) are consistent with the periods of FSMs, and the amplitude of wiggles (∆f/f ∼ 1 − 2%) implies a relatively low amplitude of the modulating MHD waves.…”
Section: Oscillations In Zebra Patternssupporting
confidence: 72%
See 1 more Smart Citation
“…Since an MHD oscillation affects the local values of the magnetic field and/or plasma density (and hence fce and/or fpe), the locations of the double plasma resonance layers are changed accordingly, which should result in periodic oscillations ("wiggles") of the zebra stripes. These wiggles were indeed observed in many events (e.g., Yu et al 2013;Kaneda et al 2018;Karlický and Yasnov 2020). The observed periods of oscillations (∼ 0.5 − 2 s) are consistent with the periods of FSMs, and the amplitude of wiggles (∆f/f ∼ 1 − 2%) implies a relatively low amplitude of the modulating MHD waves.…”
Section: Oscillations In Zebra Patternssupporting
confidence: 72%
“…Yu et al (2013) concluded that the quasi-periodic wiggles of the zebra pattern observed on 2006 December 13 were caused by a standing sausage oscillation. In contrast, Kaneda et al (2018) found that the quasi-periodic oscillations in the 2011 June 21 event can be interpreted in terms of fast sausage waves propagating upward with speeds of 3000 − 8000 km s −1 . Using observations of wiggles in the zebra pattern on 1999 February 14, Karlický and Yasnov (2020) estimated the levels of magnetic field and plasma density turbulence as ∼ 10 −3 − 10 −2 , and found indications that the turbulence was anisotropic.…”
Section: Oscillations In Zebra Patternsmentioning
confidence: 87%
“…This interpretation is supported by the forward modelling of the observational manifestation of a sausage oscillation in the gyrosynchrotron emission performed by Kuznetsov et al (2015). One-second quasi-periodic wiggles of microwave zebra patterns during a solar flare (Yu et al, 2013;Kaneda et al, 2018) have also been associated with sausage oscillations on the basis of forward modelling (Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 63%
“…In the leaky regime, the oscillation period is also determined by the transverse fast wave transit time across a coronal plasma nonuniformity such as a coronal loop (e.g., Vasheghani Farahani et al 2014;Chen et al 2016;Guo et al 2016). Sausage oscillations have already been used for the interpretation of 9 and 15 s QPP of gyrosynchrotron emission in a flaring loop (Melnikov et al 2005), and 1 s quasi-periodic wiggles of microwave zebra patterns during a solar flare (Yu et al 2013;Kaneda et al 2018).…”
Section: Discussionmentioning
confidence: 99%